Attaching Workers through In-Kind Payments : Theory and Evidence from Russia - Friebel, Guido (Published by Oxford University Press on behalf of the World Bank, 2014)
External shocks may cause a decline in the productivity of fixed capital in certain regions of an economy. Exogenous obstacles to migration make it hard for workers in those regions to reallocate to more prosperous regions. In addition, firms may devise 'attachment' strategies to keep workers from moving out of a local labor market. When workers are compensated in kind, they find it difficult to raise the cash needed for migration. This endogenous obstacle to migration has not yet been considered in the literature. The article shows that the feasibility of attachment depends on the inherited structure of local labor markets: attachment can exist in equilibrium only if the labor market is sufficiently concentrated. Attachment is beneficial for both employers and employees but hurts the unemployed and the self-employed. An analysis of matched household-firm data from the Russian Federation corroborates the theory.